DUAL THICK OCCLUSAL SPLINT: SHIELDER FOR SELF-INJURIOUS ORAL TRAUMA IN LESCH-NYHAN SYNDROME, A CASE REPORT - Shijee M; Ponnudurai Arangannal; Jeevarathan; .Janani Vinodhini; Madhumitha; Ramya Chellamal; Ishwarya Dhevi G R (The Bioscan, 2024)
Lesch- Nyhan Syndrome (LNS) is an X-linked disorder caused due to mutation in Hypoxanthine guanine Phospho Ribosyl Transferase (HPRT) gene. It is characterized by hyperuricemia, neurobehavioral issues, motor impairment and self-injurious behaviour (SIB). SIB such as lip biting and tongue biting causes deformity of the oral and perioral tissues. A lot of approaches have been tried so far to control this behaviour with variable success rates. This case report presents a 15 year old boy demonstrating the typical LNS with self-biting of lower lip and tongue. An occlusal splint using soft thermoplastic splint material which avoided the forceful contact of teeth with his lower lip and tongue was fabricated and inserted which helped in the healing of the traumatic lesions.